Tratamentos de superfícies em Ti-CP, Ti-6Al-4V e Ti-6Al- 7Nb visando a osseointegração de implantes: propriedades das superfícies e respostas osteoblásticas - Oliveira, Diego Pedreira de (Universidade Federal de São Carlos, 2013)
The aim of this study was to evaluate the properties of the surfaces of CP-Ti, Ti-6Al-4V, Ti-6Al-7Nb alloys modified via chemical treatments, as well as evaluating the behavior of human osteoblastic cells as function of these changes. For this purpose, samples of the three alloys were etched with hydrochloric acid or phosphoric acid, followed or not by alkaline treatment, and subsequently analyzed their morphology, roughness, effective area and contact angle (wettability). Scanning electron microscopy (SEM) was used to evaluate the morphology of surfaces and EDS for chemical compositions. Roughness and effective area measurements were performed with confocal laser microscope. A goniometer was used for the measurement of contact angle. Osteoblastic responses were evaluated by means of the technique of polymerase chain reaction with reverse transcription real-time (real-time PCR) to determine the gene expression of ALPL, COL1A1, COL3A1, SPP1, RUNX2 and SPARC. The results showed that the treatments significantly change the surface properties and induced the gene expression of human osteoblasts. All treatments caused change in the chemical composition of the sample surface. Acid treatments caused changes in actual topography and area, while alkaline treatments altered the surface morphology and increased hydrophilicity compared to the only abraded samples (controls). The gene expression was regulated differently in accordance with the surface treatment employed in the samples tested. Overall, treatment with alkaline treatment and phosphoric acid are more effective to control cell behavior. The alkali treatment and acid treatments together induce changes in the topography at micro, submicron and in some cases nanometric scales, which may amplify and accelerate the response of the cells on the materials.
Surface modification of Ti-CP, Ti-6Al-4V e Ti-6Al-7Nb aiming osseointegration of implants: surface properties and osteoblastic responses
Keywords: Metais; Ligas de titânio; Tratamento químico; Biocompatibilidade; Expressão gênica; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA